A multi-level perspective on the legitimacy of collaborative water governance in Québec. Issue 3 (2nd July 2016) - Orr, Christopher J.; Adamowski, Jan F.; Medema, Wietske; Milot, Nicolas
Abstract : Collaborative governance entails a shift in emphasis from government control toward voluntary arrangements directly involving non-state stakeholders in decision-making. However, the sources of legitimacy for novel institutions such as collaborative water governance remain unclear. Three levels of decision-making that are highly relevant to understanding legitimacy in these contexts are identified and used to assess the legitimacy of collaborative water governance in Québec, Canada. Using Beetham's dimensions of legitimacy – legality, justification and consent – the sources and deficits of legitimacy are identified through 35 in-person interviews with local stakeholders, watershed organization staff and provincial policy-makers. Findings illustrate the diverse sources of legitimacy, but also a disconnect between what constitutes legitimacy according to local stakeholders and the provincial government. Deficits in legitimacy include lack of implementation, misfit between collaborative governance and existing representative government, and lack of consent from the Québec government. However, although collaborative governance may not be appropriate for all contexts, it addresses important social needs that government cannot and therefore has high potential to complement the roles of existing institutions. Providing several novel insights, this multi-level perspective illustrates how legitimacy can be used to understand the challenges of complex sociological phenomena such as collaborative governance.